Akselerasi Kesiapan Membaca: Pelatihan Mengenal Dua Suku Kata Melalui Media Visual di PAUD An-Nisa - Siti Alisyah Mohu; Nunung Suryana Jamin; Icam Sutisna; Sulastya Ningsih; Sri Indrawati Zakaria; Nur Salsabila Amara; Salwa Djailolo (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Early literacy readiness is a fundamental foundation for children's language development and future academic success. This community service program aimed to accelerate reading readiness through two-syllable word recognition training using visual media at PAUD An-Nisa, Gorontalo City. The activity involved children aged 4–5 years and adopted a participatory learning through play approach supported by word cards and familiar object illustrations. Data were collected through participatory observation focusing on word recognition, picture-word matching, verbal responses, learning engagement, and the level of assistance required during activities. The findings revealed improvements in children's ability to recognize and pronounce two-syllable words, connect written symbols with visual representations, and participate actively in learning tasks. High levels of enthusiasm, concentration, and verbal interaction were consistently observed throughout the program. Individualized scaffolding also facilitated broader participation and supported the development of learning independence. The integration of visual media, play-based learning, and differentiated support effectively strengthened early reading readiness among young children.